Modified bolster dressing with continuous suction improves skin graft survival for an oral cavity wound - Eunkyu Lee; Song I Park; Donghyeok Kim; Hokyung Jin; Han-Sin Jeong (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Skin engraftment of intraoral defects is known to be inconsistent due to mobility of the oral structure, uneven wounds, and accumulation of saliva under the skin graft. To improve the success rate of oral skin graft, we proposed a novel and simple dressing technique for intraoral skin graft to control saliva accumulation, in comparison with the conventional bolster dressing. Methods We retrospectively reviewed 31 patients reconstructed with skin graft in their intraoral defect. The patients were divided into two groups; conventional bolster group (n = 21) and modified bolster group (n = 10). In the modified bolster group, a polyvinyl alcohol sponge was designed to fit the skin graft and a suction drain was inserted with tagging suture to apply continuous suction. We analyzed the success rate, the size of the skin grafts and clinical variables of each method. Results The overall success rate of oral skin graft was not different between the two groups (90.0 and 90.5%). However, partial necrosis in the engrafted skin was observed frequently in the control group (57.1% versus 20.0%). The relative engrafted area was significantly higher in the modified bolster group (55.0 ± 11.6% versus 23.0 ± 18.7%, p = 0.015). The duration of bolster dressing and the time to start an oral diet were shorter in the modified bolster group. Conclusions Our modified method could be easily applied for removing saliva accumulation under a skin graft and for enhancing skin engraftment of an oral cavity wound.